If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -5) = 52 Reorder the terms: 4(-5 + 2x) = 52 (-5 * 4 + 2x * 4) = 52 (-20 + 8x) = 52 Solving -20 + 8x = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 8x = 52 + 20 Combine like terms: -20 + 20 = 0 0 + 8x = 52 + 20 8x = 52 + 20 Combine like terms: 52 + 20 = 72 8x = 72 Divide each side by '8'. x = 9 Simplifying x = 9
| 8(6+8v)-2v=172 | | 21/b=147/105 | | -3t=8t | | (2x-5)=52 | | 4.3x+8x=12.3 | | 8a+6r=4.7 | | 4/(-5)=2x-1/2 | | q=250-5p | | 2p+6=4p+10 | | 15z=-9z | | 7(-3n-4)+2n=-123 | | y=4x^2+27x-7 | | -29=5w+6-12w | | 10t-3t-1=13 | | 81=0.5h(6+3) | | -7r+3(8r+3)=-127 | | 70+5y-2y=3 | | x/4+2=3x/2-3 | | 11x+14=94-16x | | 7(c+3)=(8c-14) | | x^2+y^2+8x-6y+16=0 | | -3/4x-5/2=-5/8+2x | | (6x-7)(9x+4)=0 | | 1(15)=(6x)(4) | | 18m+8-16=118 | | 5x+3=3(2x+4) | | 19y=29/3 | | 0=-5x-2x | | 18m+8=118 | | 7x^2+8x-15=0 | | 7d+6b=27 | | .66x-.25=.6x+1 |